A landscape and landscape biography approach to assessing the consequences of an environmental policy implementation. (18th May 2020) - Spicer, E. Anne; Swaffield, Simon; Moore, Kevin
ABSTRACT: Assessing outcomes of agri-environmental policy implementations is complex. Traditional parametric methods such as using key indicators can miss outcomes that are displaced in time and space, seldom account for the integrated nature of social and biophysical dynamics, and may overlook unintended consequences. This project aimed to overcome these drawbacks by using a landscape biography approach to analyse an innovative agri-environmental policy experiment around Lake Taupo, New Zealand. Landscape biographies were developed for each of three embedded cases, analysed as socio-ecological systems focused on relationships at different spatial scales. Landscape development paths were identified and a future trajectory estimated. The multiscale approach revealed unforeseen consequences of the policy regime, enabled a more comprehensive portrayal of social and landscape outcomes, and made complex interactions and processes understandable and accessible.